Managing Stressed Employees at Milk and Dairy Suppliers in East Africa: Evidence from Southwestern Uganda - Mucunguzi, Innocenti; Sekiwu, Denis; Les, Hirst (East African Journal of Business and Economics, 2023)
Milk production systems are intensifying due to market dynamics and increasing rivalry for production components, necessitating a correct comprehension of the new production tendencies and little effort have been done. More than 1.3 billion people are employed by it, and it generates around 40% of the world’s agricultural gross domestic product. In Uganda, the dairy milk industry contributes 80% of the gross domestic product and this plays a crucial role in the lives of many Ugandans as a source of food, income, and work. The aim of this study is rethinking how to manage stressed employees at milk and dairy suppliers. It was guided by specific objectives which include; assessing the challenges facing workers and suggesting possible solutions to ease the proper working environment. It was found that currently, roughly 14.2 million cattle, 16 million goats, 4.5 million sheep, 47.6 million chickens, and 4.1 million pigs account for the livestock production in Uganda. Work-family conflicts, poor supervisors at work, poor counselling at departmental levels by the managers were the major challenges affecting employees at milk and dairy suppliers. In addition, employees have a feeling of belonging after being given a voice, which promotes solid working relationships and this reduces stress at work.
Keywords: Livestock production; Communication; Business industry; Domestic products